Sikap Muslim Terhadap Isu Seni Figuratif - Hamidon, Nor Azlin (Jurnal Usuluddin, 2000)
This study tries to examine an Islamic perspective on the figurative art based on historical and al-Qur'an and al-Hadith points of view. It proposes that any research on Islamic art, especially the cross-cultural research, had to consider the hermeneutical and phenomenological approach.